Desenvolvimento e avaliação tecnológica na construção e manutenção de pontes de madeira na Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The construction of wooden bridges plays a crucial role in the connectivity and accessibility of communities in the Amazon. The objective of this research is to present a technological study for the implementation of a forest management lending area to support the construction and maintenance of wooden bridges in the Amazon region. The research database was generated through a technical-scientific expedition inspecting wooden bridges on BR-319 (Manaus-Porto Velho Highway) at km 263 and km 271, spanning the Bandeirão and Beleza streams, with lengths of 30.00 and 24.00 meters, respectively. The studies were conducted by the National Institute of Amazonian Research, State University of Amazonas (UEA), and the University of São Paulo (USP), with support from the INCT Amazonian Woods project. To verify wood lending areas, data from a small-scale sustainable forest management plan in the Morena Sustainable Development Project (PDS), located in the municipality of Presidente Figueiredo, Amazonas, were utilized. During the expedition, the level of protection of the bridges against natural degradation, the wood species used in bridge construction, the presence of xylophagous insects and fungi, the degree of wear on the pillars and types of connecting elements were assessed. Additionally, load tests were conducted, and the impact of the bridge on surrounding communities was examined. The research yielded robust information, highlighting the potential implementation of a small-scale management area for lending wood species for bridge construction and maintenance in the Amazon. The selection of forest management areas for bridge construction and maintenance requires a technical and scientific approach. Feasibility incorporates technical, environmental, and socio-economic principles and foundations.
Keywords: Projetos de desenvolvimento florestal; Pontes de madeira; Sustentabilidade e meio ambiente - Amazônia; CIENCIAS AGRARIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL: MANEJO FLORESTAL; CIENCIAS AGRARIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL: TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS; Manejo Florestal; Tecnologia da Madeira; Sustentabilidade; Metodologia BIM; Amazônia